MEMBANGUN KEDISIPLINAN SISWA DALAM PANDANGAN HINDU - Ketut Bali Sastrawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Teachers are human figures who occupy positions and play an important role ineducation. Teachers in the context of Hinduism have a very noble position. Even the holy book ofHinduism describes a lot about how a student must respect his teacher. The form of discipline ofa student at school can be seen from how much he appreciates his teacher. Schools should beused as a place for students to hone their discipline. Once the importance of a student to respectthe teacher according to Hinduism, requires the school to make a rule that supports it. Synergybetween parents and teachers in building student discipline is very necessary. Teachers in schoolsplay a role in controlling their discipline in school while parents at home play a role in monitoringstudents' discipline at home.